Twelve‐week secukinumab treatment is consistently efficacious for moderate‐to‐severe psoriasis regardless of prior biologic and non‐biologic systemic treatment: Post hoc analysis of six randomised trials. (9th February 2021) - Hampton, P.; Halliday, A.; Aassi, M.; Subramanian, S.; Jain, M.; Griffiths, C.E.M.
Abstract: Background: The efficacy of biologic therapies is greater among biologic‐naïve vs. biologic‐experienced psoriasis patients. However, little is known as to whether prior use of other systemic therapies impacts secukinumab efficacy in patients with moderate‐to‐severe psoriasis. Objective: To investigate the impact of prior exposure to systemic therapies upon the efficacy and safety of secukinumab 300 mg for moderate‐to‐severe psoriasis. Methods: Post hoc analysis of six randomised controlled trials (RCTs) comparing secukinumab with placebo, ustekinumab or etanercept at 12 weeks of treatment. Data comparing secukinumab with placebo and ustekinumab were meta‐analysed, while comparisons between secukinumab and etanercept were from a single RCT. Four subgroups of patients were assessed: (i) naïve to non‐biologic systemics (NBS) and biologics; (ii) exposed to NBS but naïve to biologics; (iii) naïve to NBS but exposed to biologics; and (iv) exposed to NBS and biologics. Outcomes of interest included the following: investigator's global assessment (IGA) score, absolute psoriasis area and severity index (PASI) response, PASI 75, PASI 90 and PASI 100 responses, and dermatology life quality index (DLQI). Safety was also assessed. Results: One thousand three hundred and eighty‐three patients were included in the secukinumab vs. placebo meta‐analysis: 1776 in the secukinumab vs. ustekinumab meta‐analysis and 653 in the within‐trial analyses of secukinumab vs. etanercept. For all subgroups, secukinumab was significantly more efficacious than placebo for all outcomes measured. Secukinumab generated greater responses in biologic‐naïve patients, while prior NBS had a negligible impact on treatment response. Furthermore, secukinumab was more efficacious than both ustekinumab and etanercept on many outcomes, with an even greater difference for biologic‐naïve than biologic‐exposed patients. Safety results were consistent with individual clinical trial results. Conclusions: Twelve‐week treatment with secukinumab 300 mg is consistently more efficacious than placebo, etanercept and ustekinumab in patients with moderate‐to‐severe psoriasis, regardless of prior exposure to biologics or NBS. Secukinumab had a comparable safety profile to both etanercept and ustekinumab.